How do you find the derivative of sinx(tanx)sinx(tanx)?

1 Answer
Mar 29, 2018

d/dx(sinxtanx)=cosxtanx+sinxsec^2xddx(sinxtanx)=cosxtanx+sinxsec2x

After simplification ->sinx+tanxsecxsinx+tanxsecx

Explanation:

Use the product rule.

(uv)'=u'v+uv'

u=sinx, v=tanx

Therefore

d/dx(sinxtanx)=(d/dxsinx)tanx+sinx(d/dxtanx)

=cosxtanx+sinxsec^2x

We could simplify this answer a bit by using some basic trig identities:

=cancelcosx(sinx/cancelcosx)+sinx(1/cos^2x)

=sinx+sinx/cosx(1/cosx)

=sinx+tanxsecx